A Narrative Examination of the Effects, Difficulties, and Adaptation Techniques of Climate Change on Medical Laboratory Operations - Alazeeri, Noorah Mohammed; Alanazi, Rafeef Nasser; Alqahtani, Mohammed Ali; Alhafaf, Ahmed Mohammed; Alzamil, Israa Fahad; Alqarni, Asma Nasser; Asiri, Raghad Mohammed; Alrashidi, Fares Maqbel (Journal of Posthumanism, 2025)
Globally, medical laboratory operations are being progressively disrupted by climate change, which has an impact on supply chain stability, infrastructural integrity, and diagnostic accuracy. Puerto Rico, a significant center for the production of medical supplies, was severely damaged by Hurricane Maria in 2017, which resulted in severe shortages of blood bags and reagents in American hospitals. The stability of temperature-sensitive reagents and biological samples has also been threatened by rising global temperatures; research shows that even a 2°C increase in ambient temperature can dramatically lower enzyme activity in diagnostic tests. Concerns regarding the accuracy of test results in illness diagnosis and monitoring are raised by laboratories' inability to maintain ideal storage conditions, especially in settings with limited resources. These difficulties are made worse by extreme weather and changing disease trends. Microbiology labs in South Asia have frequently been disturbed by flooding, which has resulted in waterborne pathogen contamination and delays in testing for infectious diseases. Rising temperatures in Sub-Saharan Africa have increased the range of mosquitoes that spread malaria, driving up demand for diagnostic services beyond what many labs can handle. As seen during the COVID-19 pandemic when heatwaves impacted the manufacture and shipping of medical reagents, supply chain disruptions brought on by climate-related disasters have resulted in protracted shortages of crucial testing materials. In order to guarantee laboratory resilience and continuity in healthcare services, climate-adaptive solutions are desperately needed. Laboratories must implement sustainable operational procedures and infrastructure to lessen these effects. Important suggestions include investing in climate-resilient laboratory buildings, improving digital diagnostic capabilities to lessen reliance on physical sample transportation, and switching to solar-powered refrigeration to prevent sample degradation during power outages.